 For every

X 2

Q

i

2

n

F

(

A

i

)

X 2

GR

f

,

\

Y

i

2

n

atoms

X

i

=

/

;

:

(4)

Proof.

[FIXME: ??Use of unproved conjecture

?

.]

By the theorem

11

(used that it is a boolean lattice) we have

X 2

GR

f

,

GR

f

\

Q

i

2

n

atoms

X

i

=

/

;

and thus (

4

). From this also follows uniqueness.

It is left to prove that there exists a completary staroid

f

such that

f

is a continuation of

.

Consider the relation

f

dened by the formula

X

2

f

,

\

Q

i

2

n

atoms

"

A

i

X

i

=

/

;

.

I

0

t

I

1

2

f

,

\

Q

i

2

n

atoms

"

A

i

(

I

0

i

t

I

1

i

) =

/

; ,

\

Q

i

2

n

(

atoms

"

A

i

I

0

i

[

atoms

"

A

i

I

1

i

) =

/

;

.

Thus by the lemma

I

0

t

I

1

2

f

, 9

c

2 f

0

;

1

g

n

:

\

Q

i

2

n

atoms

"

A

i

I

c

(

i

)

=

/

; , 9

c

2 f

0

;

1

g

n

:

(

i

2

n

:

I

c

(

i

)

i

)

2

f

. Trivially if

9

i

2

n

:

X

i

= 0

then

X

2

/

f

. So

f

is a completary staroid.

Let

a

2

Q

atoms

F

(

A

i

)

.

The reverse of (

3

is obvious. So we have

a

2

, 8

A

2

a

:

\

Q

i

2

n

atoms

"

A

i

A

i

=

/

; , 8

A

2

a

:

A

2

f

, 8

A

2

a

:

A

2

f

,

a

f

,

a

2

f

. Thus

f

is a continuation of

.

h

f

0

f

1

i

x

=

F

fh

f

0

i

X

FCD

h

f

1

i

X

j

X

2

atoms

x

g

h

(

f

0

f

1

)

¡

1

i

y

=

h

f

0

¡

1

i

dom

y

u h

f

1

¡

1

i

im

y

(not only for atomic

y

):

h

(

f

0

f

1

)

¡

1

i

y

=

F

fh

(

f

0

f

1

)

¡

1

if

p

g j

p

2

y

g

=

F

fh

f

0

¡

1

i

dom

f

p

g u h

f

1

¡

1

i

im

f

p

g j

p

2

y

g

=

F

fh

f

0

¡

1

i

dom

f

p

g j

p

2

y

g u

F

fh

f

1

¡

1

i

im

f

p

g j

p

2

y

g

=

h

f

0

¡

1

i

dom

y

u h

f

1

¡

1

i

im

y

It seems that these are not components of a funcoid.

Conjecture 27.

Let

R

is a set of staroids of the form

i

2

n

:

F

(

A

i

)

where every

A

i

is a boolean

lattice. If

x

2

Q

i

2

n

atoms

F

(

A

i

)

then

x

2

GR

d

R

, 8

f

2

R

:

x

2

f

.

Proof.

Let denote

x

2

, 8

f

2

R

:

x

2

f

for every

x

2

Q

i

2

n

atoms

F

(

A

i

)

. For every

a

2

Q

i

2

n

atoms

F

(

A

i

)

8

X

2

a

:

\

Q

i

2

n

atoms

"

A

i

X

i

=

/

; , 8

X

2

a

9

x

2

Q

i

2

n

atoms

"

A

i

X

i

:

x

2

, 8

X

2

a

9

x

2

Q

i

2

n

atoms

"

A

i

X

i

8

f

2

R

:

x

2

f

) 8

X

2

a; f

2

R

9

x

2

Q

i

2

n

atoms

"

A

i

X

i

:

x

2

f

) 8

X

2

a; f

2

R

:

X

2

f

, 8

f

2

R

:

a

f

, 8

f

2

R

:

a

2

f

,

a

2

.

So by the previous theorem

can be contimued till

p

for some staroid

p

of the form

i

2

n

:

P

(

f

i

)

.

Let's prove

p

=

d

R

.

x

2

p

,

x

2

)

x

2

f

for every

f

2

R

and

x

2

Q

i

2

n

atoms

F

(

A

i

)

. Thus

p

f

. Consequently

8

f

2

R

:

p

f

.

Suppose that

q

is a staroid of the form

i

2

n

:

P

(

A

i

)

such that

8

f

2

R

:

q

f

. Then for every

x

2

Q

i

2

n

atoms

F

(

A

i

)

we have

x

2

q

) 8

f

2

R

:

x

2

f

,

x

2

,

x

2

p

. So

q

p

that is

q

p

.

We have proved

p

=

d

R

. It's remained to prove that

x

2

p

, 8

f

2

R

:

x

2

f

for every

x

2

Q

i

2

n

atoms

F

(

A

i

)

. Really,

x

2

p

,

x

2

, 8

f

2

R

:

x

2

f

.

Example 28.

There exists a multifuncoid on power sets, which is not a completary multifuncoid.

Proof.

Let arity

f

=

N

and form

f

= (

P

f

0

;

1

g

)

N

.

Characteristic function of a set

D

is

(

D

) =

i

2

N

:

f

1

g

if

i

2

D

;

f

0

g

if

i

2

/

D:

GR

f

=

f

(

D

)

j

D

2

g

.

Obviously

f

is an anchored relation.

Let

k

2

N

.

(

val

f

)

k

L

=

f

X

2

(

form

f

)

k

j

L

[ f

(

k

;

X

)

g 2

GR

f

g

=

f

X

2

(

P

f

0

g

)

N

j 9

D

2

:

L

[ f

(

k

;

X

)

g

= (

D

)

g

=

f

X

2

(

P

f

0

;

1

g

)

N

j 9

D

2

: (

L

= (

D

)

j

N

nf

k

g

^

X

= (

D

)(

k

))

g

.

X

2

(

val

f

)

k

L

, 9

D

2

: (

L

= (

D

)

j

N

nf

k

g

^

X

k

= (

D

)(

k

))

,

??

, 9

D

2

N

nf

k

g

; P

2 ff

0

g

;

f

1

gg

:

(

L

= (

D

)

^

X

k

=

P

)

, 9

D

2

N

nf

k

g

:

L

= (

D

)

^ 9

P

2 ff

0

g

;

f

0

;

1

gg

:

X

k

=

P

, 9

D

2

N

nf

k

g

:

L

= (

D

)

^

X

2 ff

0

g

;

f

1

gg

(Note it does not depend on

X

.)

Let

X ; Y

2

(

P

f

0

;

1

g

)

N

. Then

X

t

Y

2

(

val

f

)

k

L

, 9

D

2

N

nf

k

g

:

L

= (

D

)

^

X

t

Y

2 ff

0

g

;

f

1

gg

Rest

9